ETIKA DAN KEADILAN PAJAK DALAM PERSPEKTIF ISLAM - Daryanti, Daryanti; Asriyana, Asriyana; Hasti, Astuty (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2024)
From an Islamic perspective, taxes must be managed fairly and proportionally. Taxes imposed must take into account people's ability to pay so that they do not burden the lower and upper middle classes. Apart from that, the use of tax funds must be transparent and used for public interests that benefit the entire community. This research aims to analyze tax ethics and justice from an Islamic perspective. Taxes are an important source of state revenue, but there are often debates regarding ethics and fairness in the tax system. This research is conceptual research using the literature review method. The data used in this research is secondary data. This research provides an important contribution to understanding tax ethics and justice from an Islamic perspective. The implication of this research is the need to apply Islamic principles in the formulation of fairer tax policies. It is hoped that the results of this research can become a reference for the government and policymakers in designing a taxation system that is in accordance with Islamic values and provides maximum benefits for society.